2020
DOI: 10.1002/ejoc.202000966
|View full text |Cite
|
Sign up to set email alerts
|

Shining Light on TiIV Complexes: Exceptional Tools for Metallaphotoredox Catalysis

Abstract: Titanium is one of the most abundant and environmentally innocuous metals. Ti-based organometallic compounds have long been used as versatile homogeneous catalysts in synthetic chemistry and still remain highly attractive for the development of sustainable transformations. With the emerging role of photoredox catalysis, the selectivity of the radical initiation in electron transfer-mediated reactions has been

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 113 publications
(121 reference statements)
0
22
0
Order By: Relevance
“…Early on, [Cp* 2 ScCl] was found to emit in fluid solution at room temperature with a luminescence lifetime of 2.0 μs and the emissive excited state was assigned as LMCT from the p -Cl nonbonding lone pair to the Sc 3+ ion. , Many Ti IV based metallocenes with the general formula Cp 2 TiX 2 also exhibit LMCT luminescence, albeit typically only in the solid state at 77 K . More recently, this compound class has become of interest for photoredox catalysis. , A Ti IV carbene complex seemed to be nonemissive in solution at room temperatures while its Zr IV and Hf IV analogues emitted under these conditions . Recent work on related work focused much on Zr IV (and comparatively little on Ti IV ), suggesting that room temperature emission is much more tricky to obtain for Ti IV than for Zr IV . , …”
Section: Lmct Emitters: 3d0 (Sciii) 3d3 (Mniv) 3d5 (Feiii) and 3d6 (C...mentioning
confidence: 99%
“…Early on, [Cp* 2 ScCl] was found to emit in fluid solution at room temperature with a luminescence lifetime of 2.0 μs and the emissive excited state was assigned as LMCT from the p -Cl nonbonding lone pair to the Sc 3+ ion. , Many Ti IV based metallocenes with the general formula Cp 2 TiX 2 also exhibit LMCT luminescence, albeit typically only in the solid state at 77 K . More recently, this compound class has become of interest for photoredox catalysis. , A Ti IV carbene complex seemed to be nonemissive in solution at room temperatures while its Zr IV and Hf IV analogues emitted under these conditions . Recent work on related work focused much on Zr IV (and comparatively little on Ti IV ), suggesting that room temperature emission is much more tricky to obtain for Ti IV than for Zr IV . , …”
Section: Lmct Emitters: 3d0 (Sciii) 3d3 (Mniv) 3d5 (Feiii) and 3d6 (C...mentioning
confidence: 99%
“…12 Recently, Gansäuer, 13 our group, 14 and Shi 15 have reported the generation of [Ti( iii )] under photoredox conditions for radical chemistry (allylation reactions, 14 a ,15 b opening of epoxides, 13,15 a propargylations 14 b ). 16 Unfortunately, any attempt to use organic dyes, 17 as well as [Ru( ii )] or [Ir( iii )] photocatalysts, with [Ti( iv )] complexes, in the presence of Hantzsch's ester or amine-based reductants, gave almost a 1 : 1 ratio of the diastereomeric diols in a model reaction with p -chlorobenzaldehyde. This was probably due to a fast and effective reaction performed by the photoredox catalysts, with no participation of the titanium complex.…”
Section: Introductionmentioning
confidence: 99%
“…Assignment of excited states in the related titanocene Cp 2 Ti­(NCS) 2 was later addressed by a combination of DFT calculations and time-resolved IR spectroscopy in a study by Kenney et al Only recently, photoredox catalysis using visible-light irradiation was demonstrated by Gansäuer and Flowers with Cp 2 TiCl 2 on reactions such as reduction of epoxides and 5-exo cyclizations of unsaturated epoxides . This approach using energy of the 3 LMCT excited state of the metallocene with a concomitant electron transfer for chemical transformations is indeed a perspective topic for future studies …”
Section: Introductionmentioning
confidence: 99%